VD_FINDINFO HC / 2013 / 446 vom 24. Mai 2013 - VD Tribunal cantonal (2013)
ASSISTANCE JUDICIAIRE, INDEMNITÉEN GÉNÉRAL | 110 CPC (CH), 122 al. 1 let. a CPC (CH), 319 let. b ch. 1 CPC (CH), 322 al. 1 CPC (CH), 2 al. 1 RAJ